Becoming Scholarly Writers through Professional Learning Community: A Phenomenological Case Study of Indonesian Teacher-Educators - Cassandra, Nina Wanda; Fithriani, Rahmah; Febriyanti, Rina Husnaini; Mukminin, Amirul (LEARN Journal: Language Education and Acquisition Research Network, 2024)
Due to the mounting pressure to publish international publications, faculty members around the globe must take the initiative to upgrade their writing capacity through various methods, including participation in workshops and training, obtaining professional support, and joining learning communities. This paper focuses on our experience, three female teacher educators, of becoming scholarly writers for international readership through PROSINAR, an Indonesia-based professional learning community (PLC). We present the PLC scheme for establishing a platform for faculty members to (re)construct and develop their professional identities. Based on findings from a phenomenological case study framed by Freire’s (1993) notion of dialogic encounters, we evaluate our professional identities as English teacher-educators while simultaneously constructing our identities as scholarly writers within our discourse community. We believe that in addition to being a platform for continuing professional development in the context of education, PLC has established itself as an emergent learning platform to improve faculties’ research competence and develop their scholarly writing capacity.